A high-speed secure quantum random number generator based on vacuum states - Gabriel, Christian; Wittmann, Christoffer; Hacker, Bastian; Mauerer, Wolfgang; Huntington, Elanor; Sabuncu, Metin; Marquardt, Christoph; Leuchs, Gerd (2012 Conference on Lasers and Electro-Optics, CLEO 2012, 2012)
A high-speed continuous-variable quantum random bit generator with an expected effective bit generation rate of up to 10 GBit/s is presented. The obtained bit sequences are truly random and unique, i.e. they cannot be known by an adversary. © 2012 OSA.
CRIS-Team Scopus Importer:2022-06-05

Atmospheric channel characteristics for quantum communication with continuous polarization variables - Heim, Bettina; Elser, Dominique Alexander; Bartley, Tim; Sabuncu, Metin; Wittmann, Christoffer; Sych, Denis; Marquardt, Christoph; Leuchs, Gerd (Applied Physics B-Lasers and Optics, 2010)
We investigate the properties of an atmospheric channel for free space quantum communication with continuous polarization variables. In our prepare-and-measure setup, coherent polarization states are transmitted through an atmospheric quantum channel of 100 m length on the flat roof of our institute's building. The signal states are measured by homodyne detection with the help of a local oscillator (LO) which propagates in the same spatial mode as the signal, orthogonally polarized to it. Thus the interference of signal and LO is excellent and atmospheric fluctuations are auto-compensated. The LO also acts as a spatial and spectral filter, which allows for unrestrained daylight operation. Important characteristics for our system are atmospheric channel influences that could cause polarization, intensity and position excess noise. Therefore we study these influences in detail. Our results indicate that the channel is suitable for our quantum communication system in most weather condition
UnivIS-Import:2015-04-14:Pub.2010.nat.dphy.optik.1optik.atmosp

A versatile source of single photons for quantum information processing - Förtsch, Michael; Fürst, Josef; Wittmann, Christoffer; Strekalov, Dmitry; Aiello, Andrea; Chekhova, Maria V.; Leuchs, Gerd; Silberhorn, Christine; Marquardt, Christoph (Nature Communications, 2013)
The generation of high-quality single-photon states with controllable narrow spectral bandwidths and central frequencies is key to facilitate efficient coupling of any atomic system to non-classical light fields. Such an interaction is essential in numerous experiments for fundamental science and applications in quantum communication and information processing, as well as in quantum metrology. Here we implement a fully tunable, narrow-band and efficient single-photon source based on a whispering gallery mode resonator. Our disk-shaped, monolithic and intrinsically stable resonator is made of lithium niobate and supports a cavity-assisted spontaneous parametric down-conversion process. The generated photon pairs are emitted into two highly tunable resonator modes. We verify wavelength tuning over 100 nm of both modes with controllable bandwidth between 7.2 and 13 MHz. Heralding of single photons yields anti-bunching with g (2) (0)<0.2. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Device Calibration Impacts Security of Quantum Key Distribution - Jain, Nitin; Wittmann, Christoffer; Lydersen, Lars; Wiechers, Carlos; Elser, Dominique Alexander; Marquardt, Christoph; Makarov, Vadim; Leuchs, Gerd (Physical Review Letters, 2011)
Characterizing the physical channel and calibrating the cryptosystem hardware are prerequisites for establishing a quantum channel for quantum key distribution (QKD). Moreover, an inappropriately implemented calibration routine can open a fatal security loophole. We propose and experimentally demonstrate a method to induce a large temporal detector efficiency mismatch in a commercial QKD system by deceiving a channel length calibration routine. We then devise an optimal and realistic strategy using faked states to break the security of the cryptosystem. A fix for this loophole is also suggested. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

Discrimination of optical coherent states using a photon number resolving detector - Wittmann, Christoffer; Andersen, Ulrik Lund; Leuchs, Gerd (Journal of Modern Optics, 2010)
The discrimination of non-orthogonal quantum states with reduced or without errors is a fundamental task in quantum measurement theory. In this work, we investigate a quantum measurement strategy capable of discriminating two coherent states probabilistically with significantly smaller error probabilities than can be obtained using non-probabilistic state discrimination. We find that appropriate postselection of the measurement data of a photon number resolving detector can be used to discriminate two coherent states with small error probability. We compare our new receiver to an optimal intermediate measurement between minimum error discrimination and unambiguous state discrimination.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.optik.1optik.discri
Keywords: Quantum information; Quantum receivers; Quantum state discrimination

Enhanced free space beam capture by improved optical tapers - Bartley, Tim; Heim, Bettina; Elser, Dominique Alexander; Sych, Denis; Sabuncu, Metin; Wittmann, Christoffer; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (2010)
In our continuous variable quantum key distribution (QKD) scheme, the homodyne detection set-up requires balancing the intensity of an incident beam between two photodiodes. Realistic lens systems are insufficient to provide a spatially stable focus in the presence of large spatial beam-jitter caused by atmospheric transmission. We therefore present an improved geometry for optical tapers which offer up to four times the angular tolerance of a lens. The effective area of a photodiode can thus be increased, without decreasing its bandwidth. This makes them suitable for use in our free space QKD experiment and in free space optical communication in general. © Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering 201
Keywords: Atmospheric optics; Beam-jitter; Free space communication; Optical taper; Quantum key distribution; Random media

Guided acoustic wave Brillouin scattering in photonic crystal fibers - Elser, Dominique Alexander; Wittmann, Christoffer; Andersen, Ulrik Lund; Glöckl, Oliver; Lorenz, Stefan; Marquardt, Christoph; Leuchs, Gerd (Journal of Physics: Conference Series, 2007)
In silica glass fibers, thermally excited acoustic phonons scatter light into the beam propagating in the forward direction. At acoustic frequencies up to several hundreds of megahertz, the wave vectors of the phonons interacting with the light propagate essentially transversally to the fiber axis. This effect is known as Guided Acoustic Wave Brillouin Scattering (GAWBS) and leads to phase and polarization noise in the guided light. For fiber-based quantum optics experiments, this excess noise is a major limitation. In Photonic Crystal Fibers (PCFs), light is guided by a microstructure simultaneously acting as a 2D transversal phononic crystal which modifies the acoustic noise spectrum. We demonstrate a GAWBS-noise reduction in commercially available PCFs. This gives rise to the prospect of fiber-based quantum optic devices exhibiting less excess noise, thus resulting in higher quantum state purity. Further improvement can be achieved by tailoring the photonic microstructure such that a reduction of phonon noise by design is achieved. © 2007 IOP Publishing Ltd.
Created from Fastlane, Scopus look-up

Noise-powered probabilistic concentration of phase information - Usuga, Mario A.; Müller, Christian; Wittmann, Christoffer; Marek, Petr; Filip, Radim; Marquardt, Christoph; Leuchs, Gerd; Andersen, Ulrik L. (Nature Physics, 2010)
Phase-insensitive optical amplification of an unknown quantum state is known to be a fundamentally noisy operation that inevitably adds noise to the amplified state. However, this fundamental noise penalty in amplification can be circumvented by resorting to a probabilistic scheme as recently proposed and demonstrated in refs 6, 7, 8. These amplifiers are based on highly non-classical resources in a complex interferometer. Here we demonstrate a probabilistic quantum amplifier beating the fundamental quantum limit using a thermal-noise source and a photon-number-subtraction scheme. The experiment shows, surprisingly, that the addition of incoherent noise leads to a noiselessly amplified output state with a phase uncertainty below the uncertainty of the state before amplification. This amplifier might become a valuable quantum tool in future quantum metrological schemes and quantum communication protocols. © 2010 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-06-05

Observation of the Geometric Spin Hall Effect of Light - Korger, Jan; Aiello, Andrea; Chille, Vanessa; Wittmann, Christoffer; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (Physical Review Letters, 2014)

Quadrature phase shift keying coherent state discrimination via a hybrid receiver - Müller, Christian; Usuga, M. A.; Wittmann, Christoffer; Takeoka, M.; Marquardt, Christoph; Andersen, U. L.; Leuchs, Gerd (New Journal of Physics, 2012)
We propose and experimentally demonstrate a near-optimal discrimination scheme for the quadrature phase shift keying (QPSK) protocol. We show in theory that the performance of our hybrid scheme is superior to the standard scheme-heterodyne detection-for all signal amplitudes and underpin the predictions with our experimental results. Furthermore, our scheme provides hitherto the best performance in the domain of highly attenuated signals. The discrimination is composed of a quadrature measurement, a conditional displacement and a threshold detector. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.
CRIS-Team Scopus Importer:2022-06-05

Superlinear threshold detectors in quantum cryptography - Lydersen, Lars; Jain, Nitin; Wittmann, Christoffer; Maroy, Oystein; Skaar, Johannes; Marquardt, Christoph; Makarov, Vadim; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2011)
We introduce the concept of a superlinear threshold detector, a detector that has a higher probability to detect multiple photons if it receives them simultaneously rather than at separate times. Highly superlinear threshold detectors in quantum key distribution systems allow eavesdropping the full secret key without being revealed. Here, we generalize the detector control attack, and analyze how it performs against quantum key distribution systems with moderately superlinear detectors. We quantify the superlinearity in superconducting single-photon detectors based on earlier published data, and gated avalanche photodiode detectors based on our own measurements. The analysis shows that quantum key distribution systems using detector(s) of either type can be vulnerable to eavesdropping. The avalanche photodiode detector becomes superlinear toward the end of the gate. For systems expecting substantial loss, or for systems not monitoring loss, this would allow eavesdropping using trigger pulses containing less than 120 photons per pulse. Such an attack would be virtually impossible to catch with an optical power meter at the receiver entrance. © 2011 American Physical Society.
CRIS-Team Scopus Importer:2022-06-05

The polarization properties of a tilted polarizer - Korger, Jan; Kolb, Tobias; Banzer, Peter; Aiello, Andrea; Wittmann, Christoffer; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2013)
Polarizers are key components in optical science and technology. Thus, understanding the action of a polarizer beyond oversimplifying approximations is crucial. In this work, we study the interaction of a polarizing interface with an obliquely incident wave experimentally. To this end, a set of Mueller matrices is acquired employing a novel procedure robust against experimental imperfections. We connect our observation to a geometric model, useful to predict the effect of polarizers on complex light fields. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05